Comparing Aboriginal community-based criteria and indicators in forest management planning - Symington-Armstrong, Erin (My University, 2018)
Criteria and indicator (C&I) frameworks have been developed and implemented on national and international scales to measure sustainable forest management. The purpose of this research is to examine the reasons why Indigenous communities would develop local-level criteria and indicator frameworks, what the process is for their development and how they are being used. Criteria and indicators were collected from published and unpublished literature for six First Nation communities. The indicators were reorganized using researcher definitions of institutional, cultural, environmental, social and economic indicators for ease of data analysis. Representatives from each of the case studies were interviewed to provide contextual information about their framework development. Indigenous indicators capture values rooted in traditional knowledge and cultural practices and seek to remedy social issues centred on community well-being. In the last decade the use of C&I in forest management is declining, but C&I still serve as an important tool to collect data and values to measure change and achieving goals, especially at the local level.
Keywords: Sustainable forest management; Traditional ecological knowledge; Community well-being; Aboriginal forestry in Canada